Pemberdayaan Ekonomi Masyarakat Di Desa Sangkima Kecamatan Sangatta Selatan Kabupaten Kutai Timur - Dormauli; Muhammad Jamal; Mohammad Taufik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The purpose of this research is to know and describe Community Economic Empowerment in Sangkima Village, South Sangatta District, East Kutai Regency. As well as to identify the obstacles found in Community Economic Empowerment in Sangkima Village, South Sangatta District, East Kutai Regency.This type of research is a qualitative descriptive research. Data collection techniques were carried out by means of library research and field research. By using the method of observation, interviews and documentation. The results of this study indicate that the economic potential in Sangkima Village, South Sangatta District is agriculture, plantations, fisheries, tourism, and MSMEs.Economic empowerment carried out by the district government is as a planner, facilitator, supervisor, and evaluator. The sub-district government acts as a facilitator between the district and village governments. And the village government includes making the community the subject and object of development, increasing community participation and carrying out empowerment such as providing training/education to the community, providing capital assistance. Constraints that occur in economic empowerment are limited capital, facilities and infrastructure and low community participation.